Penanaman Pohon Kelengkeng Sebagai Upaya Pelestarian Lingkungan dan Pemberdayaan Masyarakat di Desa Pejengkolan, Kabupaten Kebumen - Septyani Elitasari; Kafifah Ayu LestarI; Wiji Barokatul Khoeriyah; Siska Puspitasari; Hairul Anwar; Adnan Mustofa; Nova Andi Saputra; Akhmad Hamam Nasirudin; Samsubakri Samsubakri; Isnaini Lilis Elviyanti (BADAN PENERBIT STIEPARI PRESS, 2025)
The community service activity conducted in Pejengkolan Village, Kebumen Regency, was part of the 2025 Community Service Program (Kuliah Kerja Nyata or KKN) organized by Universitas Ma’arif Nahdlatul Ulama (UMNU) Kebumen. This program focused on both environmental conservation and community empowerment through socialization and the planting of longan (kelengkeng) trees. The stages of the activity included awareness sessions for the villagers about the ecological and economic benefits of longan trees, proper planting techniques, and effective maintenance strategies to ensure productive growth. In addition, a direct planting activity was carried out collaboratively, involving KKN students, local authorities, and community members. The active participation of the villagers, demonstrated through their enthusiasm in both the socialization and the practical planting sessions, indicated a strong commitment to the program’s sustainability. Through this initiative, the community not only gained new knowledge about longan cultivation but also developed motivation to harness their village’s potential in an environmentally sustainable way. The continuity of longan tree maintenance is expected to generate long-term benefits, providing ecological advantages while also offering economic opportunities for the people of Pejengkolan Village.